Β‐carotene attenuates weaning‐induced apoptosis via inhibition of PERK‐CHOP and IRE1‐JNK/p38 MAPK signalling pathways in piglet jejunum. Issue 1 (1st October 2019) - Li, Ruonan; Yang, Yu; Hong, Pan; Zhang, Ziqi; Li, Lingqian; Hui, Junnan; Zheng, Xin
Abstract: Weaning may cause oxidative injury, immune response impairment, apoptosis and other injuries in piglets. Oxidative and endoplasmic reticulum stress (ERS) can elicit inflammatory responses, and persistent oxidative and ERS also may lead to apoptotic cascades, which is associated with the pathogenesis of multiple diseases. β‐carotene, a natural carotenoid, has potential anti‐inflammatory and antioxidant functions. However, the effect of β‐carotene on apoptosis in weaned piglets and the detailed molecular mechanism remain unclear. In this study, we found that β‐carotene decreased malondialdehyde (MDA) levels and increased the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH‐Px) in piglet serum. β‐carotene could inhibit the mRNA levels of caspase‐3 significantly, but had no significant inhibitory effect of the mRNA levels of caspase‐9 and caspase‐12 in the piglet jejunum. In addition, β‐carotene decreased the activation of GRP78, CHOP, and JNK/p38 MAPK and the ratio of Bax/Bcl‐2. Furthermore, β‐carotene had a significant influence on the activation of ERS and apoptosis‐related signals in TG‐induced IPEC‐J2. In the present study, β‐carotene pre‐treatment attenuated the ratio of Bax/Bcl‐2 and prevented TG‐induced increases in the level of PERK‐CHOP and IRE1‐JNK/p38 MAPK pathway activation in a dose‐dependent manner. Overall, these findings indicate that β‐carotene may protect weaning‐induced apoptosis through inhibiting ERS.